Development and Implementation of an Oral Oncology Drug Repository Program. Issue 3 (March 2021) - Stanz, Lauren; Ulbrich, Tim; Yucebay, Filiz; Kennerly-Shah, Julie
Abstract : PURPOSE: Because of high costs associated with oral oncology drugs, patients are often unable to afford their medications. Developing and implementing an oral oncology drug repository program can provide cost savings and waste reduction opportunities to oncology patients and health care systems. METHODS: Strategies to implement an oral oncology drug repository program include the following: (1) define patient eligibility requirements for the collected drug, (2) ensure patients have long-term availability to preferred treatment, (3) identify optimal oral oncology drugs to use, (4) provide safe drug collection with protocol, (5) calculate the amount of resources needed to provide services, (6) obtain adequate space to operate safely and efficiently, (7) establish safe disposal of the drug deemed inappropriate for use, and (8) spread awareness to prospective patient participants. RESULTS: To date, The Ohio State University Wexner Medical Center oral oncology drug repository program has received 11 drug collections and has redispensed drugs several times. With additional resources, the plan is to expand the repository program's scope to include other drugs and reach more patients. CONCLUSION: Developing and implementing an oral oncology drug repository program for patients was logistically feasible due to strategic planning with many early successes. As national attention continues to be placed on reducing oral oncology drug costs, additional research is needed regarding strategies to best incorporate pharmacy services into innovative patient care opportunities.